Оптимізація дорожнього руху з використанням штучного інтелекту - Костров, Д. Р. (ХНУРЕ, 2021)
The rapid pace of developments in Artificial Intelligence (AI) is providing unprecedented opportunities to enhance the performance of different industries and businesses, including the transport sector. The innovations introduced by AI include highly advanced computational methods that mimic the way the human brain works. Moreover, it is promising for transport authorities to determine the way to use these technologies to create a rapid improvement in relieving congestion, making travel time more reliable to their customers and improve the economics and productivity.
Keywords: Оптимізація дорожнього руху; штучний інтелект